PERANCANGAN MODEL E-LEARNING PADA MATERI KEPERAWATAN BENCANA TERHADAP ANAKDI AKADEMI KEPERAWATAN TJOET NYA’ DHIENBANDA ACEH - Deviana, M. Dirhamsyah, Sri Adelila Sari. (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2014)
Abstract: This study, entitled "Designing E-learning model to Content Disaster Nursing Against Children at college of nursing Tjoet Nya’ Dhien Banda Aceh. Aims to design a model of e-learning on the matter of children in disaster nursing students Children at college of nursing Tjoet Nya’ Dhien Banda Aceh by way of e-learning validation by experts. This study is a Research and Development (R D). Methods This study starts from the data collection, naming the site (domain/subdomain), the arrangement of the display, the input content (material), to validate the site. Assessment consists of four components, namely the content, language, and presentation graphics. Whole grain components and assessment is good and fit for use. Feasibility contents we can see the results got a score of 4 (good) as much as 94.44% and a score of 3 (quite) as much as 5.56%. for linguistic got a score of 4 (good) as much as 91.67% and 8.33 remaining% got a score of 5 (very good). For presentation component 73.33% got a score of 4 (good), 13.33% received a score of 5 (very good) and the remaining 13.33% in the category with a score of 3, while sufficient for as much as 41.67% design categories are in categories with a score of 4, and 58.33% were in the excellent category or got a score of 5.Keywords:E-learning, disaster nursing, validity, college of nursing and design Abstrak: Penelitian ini berjudul “Perancangan Model E-learning Pada Materi Keperawatan Bencana Terhadap Anak di Akademi Keperawatan Tjoet Nya’ Dhien Banda Aceh” bertujuan untuk merancang model e-learning pada materi keperawatan bencana terhadap anak pada mahasiswa di Akademi Keperawatan Tjoet Nya’ Dhien Banda Aceh dengan cara validasie-learning oleh paraahli. Penelitian ini bersifat Research and Development (RD). Metode penelitian ini dimulai dari pengumpulan data,  penamaan situs( domain/subdomain), penataan tampilan, input konten(materi), hingga validasi situs. Penilaiannya terdiri dari 4 komponen, yaitu isi, kebahasaan, sajian dan kegrafisan. Seluruh komponen dan butir-butir penilaian adalah baik dan layak digunakan. Kelayakan isi dapat kita lihat hasilnya. mendapat skor 4 (baik) sebanyak 94.44% dan skor 3 (cukup) sebanyak 5.56%. untuk kebahasaan mendapat skor 4 (baik) sebanyak 91.67% dan sisanya 8.33% mendapat skor 5 (sangat baik). Untuk komponen sajian 73.33% mendapat skor 4 (baik), 13.33% mendapat skor 5 (sangat baik) dan sisanya 13.33% dalam kategori cukup dengan skor 3. Sedangkan untuk kategori kegrafisan sebanyak 41.67% berada dalam kategori baik dengan skor 4 dan58.33% berada dalam kategori sangat baik atau mendapat skor 5.Kata kunci: E-learning, keperawatan bencana, validitas, akademi keperawatan dan rancangan